KAJIAN STRUKTURAL CERPEN WA KĀNAT AD-DUNYĀ DALAM ANTOLOGI CERPEN ARINILLĀH KARYA TAUFIQ EL-HAKIM - Arief Fiddienika; Fatkhul Ulum; Rachmat Nuhidayatullah (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Structural Analysis of the Short Story of Wa Kānat Ad-Dunyā in the Anthology of the Short Story of Arinillāh by Taufiq El-Hakim. The purpose of this study is to describe: (1) intrinsic elements, (2) the relationship between elements, and (3) educational values in the short story wa kānat ad-dunyaā by Taufiq El-Hakim. This research is literary research with a text translation approach and structural theory. The data in the form of a short story "Wa Kānat Ad-Dunyā" was translated into Indonesian. After that, the data is collected based on facts and interpreted based on the structural principles of the story. Based on the research conducted, it means that the short story wa kānat ad-dunya by Taufiq El-Hakim has complete intrinsic elements from story facts, themes, and literary means. As well as the existence of relationships between elements that are mutually influencing so that they become one unified whole. In addition, there are educational values both in terms of religious values, moral values, social values, and aesthetic values.